Pengembangan Ekonomi Kreatif Berbasis Wisata Budaya: Studi Kasus pada Pengrajin Tenun di Kabupaten Sambas - Andiono, Andiono; Yuliansyah, Yuliansyah; Sumar’in, Sumar’in (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
A creative economy is based on people"™s use of their creative imagination to increase an idea"™s value. Howkins"™ creativity-based model includes all kinds of creativity, whether expressed in art or innovation. The narrower culture-based models concentrate on arts, design and media and are normally restricted to nominated industries. The problem in this research is how the concept of creative economic development, as well as forms of tourist development policies capable of stimulating the economy and incomes in Sambas district? The method used in this research is the case study approach using SWOT analysis on a matrix approach. Results from this study that the development of the creative economy in Sambas district is to improve the quality of human resources in particular culture-based creative industries such as weaving craft that emerged from the group of small and medium industries, with has a unique and sale value.